Relationship between SPP1 (Osteopontin) and extracellular matrix dynamics: a comprehensive review - Liu, Ying; Yan, Xiaoyan; Fan, Rui (Frontiers in Medicine, 2025)
BackgroundSecreted Phosphoprotein 1 (SPP1), which encodes Osteopontin, a key member of the SIBLING family, is a multifunctional ECM glycoprotein and cytokine. Its interaction with collagen and other ECM components drives pathological remodeling across multiple diseases, yet a unified mechanistic framework remains elusive.ObjectiveThis review synthesizes current evidence on SPP1-mediated ECM dysregulation, focusing on collagen deposition, epithelial-mesenchymal transition (EMT), and fibrosis, with the goal of elucidating its role as a central pathological hub.MethodsWe synthesize the findings from multi-omics analyses (single-cell RNA sequencing, spatial transcriptomics), machine learning, and in vivo/in vitro experimental studies, aiming to elucidate the role of SPP1 (Osteopontin) in the dysregulation of the extracellular matrix (ECM) across various diseases via a systematic literature review (1990–2025).ConclusionSPP1 is a master regulator of pathological ECM dynamics, driven by conserved SPP1+ macrophage-ECM interactions. Targeting the SPP1-collagen axis may offer unified strategies for fibrosis and metastasis suppression. Future work should prioritize in vivo validation in osteoarthritis and clinical translation of SPP1-directed therapies.